Determinación de los desechos de la producción bananera en el cantón Arenillas - Pindo Velepucha, Stalin Antonio (2012)
This proyect about determination of the residues of the banana production it carried out in the Arenillas cantonment in the province El Oro, in forty eight selected farms to random between expert and half- expert, them were visited in different days along of six months during the process of loading to record the relative information about to harvest bunches for week, amount of residues of reject fruit, weight of raquis use of suncho to prop up the plants, number of covers protectors bow ties, cujes kind of exported boxes, total of boxes first- rate processed for farm, total of exported and processed, percent of fruit to internal market, weekly conversion. The opinion polls to permited to obtain facts of the fruit, quantification and the fate of the residues of this activity the organic biodegradable residues that produce in the farms in Arenillas cantonment, it to enter annual for thousands of tonels, that at the moment do not to used correctly, the pollution of the ground in the region it produce because to remain residues of plastic material that produce negative Impacts in the structure and to generate source of microorganism, specially fungus to cause of illness in the plants and banana workers. The obtained remains of the bunches of banana it appreciate between the 9,82 to 9,39 of raquis and 6,67 to 7,48 percent of reject fruit to expert banana farms and half- expert respectively, in the second case the remain join to the fruit of the rejected bunches, depending of the period, it process like box of second kind and in others periods sold to customers to the internal consumption such of people as of animals or in the worst case to put it in secret rubbish dump to causing a serious pollution and bad image. The hierarchicalization in expert banana farms and half- expert, do not consider the MAGAP and AGROCALIDAD, because the production of banana to involve some technology in the fertilization, use of crop, control to quality of the fruit and of the black sigatoka. The real possibilities to low the pollution is by means the application of laws that adjust the environment and the persuading of the producers about the negative impacts that produce the banana industry and the adoption of compensated measurement. There are the real possibilities to process the raquis of banana to the manufacture to organic fertilizer of acceptable quality and generalized development of the agriculture And finally as a real possibility to manufacture methyl alcohol to combustible